Turkish Republic of Northern Cyprus as a De Facto and Limited Recognized State: From Federal Solution to Two State Model - M. T. Özsağlam (Международная аналитика)
This study covers the history of the Turkish Republic of Northern Cyprus (TRNC) as a de facto state, a status it has held since 1983 after having established its institutional structure in 1975 under the name of the Turkish Federated State of Cyprus (TFSC). The TRNC has unique characteristics when compared with other de facto states. While it is home to EU citizens, it enjoys the support and influence of Turkey as its patron state, which is not member of the European Union. Although the TRNC has been declared an independent state, TRNC leaders pursued a federal solution to reunify the island until E. Tatar was elected president in 2020. The TRNC has another unique characteristic: its civil society tradition is more powerful than opposition political parties and non-governmental organizations, which sometimes clash with the government of Turkey concerning the latter’s policies in the TRNC and the Cyprus question. As the TRNC’s patron state, Turkey shapes its stance on the island in parallel with its relations with the European Union. The lack of any progress on Turkey’s EU membership and uncompromising position of the Greek Cypriot leadership at negotiations in recent decades have pushed Turkey to shift its position on the Cyprus problem. Therefore, after coming to power, Tatar stated that a federal solution is not possible on the island and insisted that a two-state model be implemented with the support of Turkey.